1998
DOI: 10.1088/0268-1242/13/5/005
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the influence of high currents on the cutoff frequency in Si/SiGe/Si heterojunction transistors

Abstract: A one-dimensional self-consistent bipolar Monte Carlo simulation code has been used to model carrier mobilities in strained doped SiGe and the base-collector region of Si/SiGe/Si and SiC/Si heterojunction bipolar transistors (HBTs) with wide collectors, to study the variation of the cutoff frequency f T with collector current density J C . Our results show that while the presence of strain enhances the electron mobility, the scattering from alloy disorder and from ionized impurities reduces the electron mobili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…(1), e is the elementary charge, is the reduced Planck's constant, m* is the electron effective mass, f 10 is the oscillator strength, f(E) is the Fermi distribution function, which is calculated for a chosen sheet carrier concentration (N s ), and E 10 is the intersubband energy difference. This energy difference is calculated by solving the Schrödinger equations in the well and barrier regions considering different masses for well and barrier [25].…”
Section: Theorymentioning
confidence: 99%
“…(1), e is the elementary charge, is the reduced Planck's constant, m* is the electron effective mass, f 10 is the oscillator strength, f(E) is the Fermi distribution function, which is calculated for a chosen sheet carrier concentration (N s ), and E 10 is the intersubband energy difference. This energy difference is calculated by solving the Schrödinger equations in the well and barrier regions considering different masses for well and barrier [25].…”
Section: Theorymentioning
confidence: 99%
“…The above analytical equations were used to demonstrate the formation of the parasitic electron barrier in Si/Si 0.8 Ge 0.2 /Si HBTs with base doping of 5 × 10 18 cm −3 and a 7500 Å-thick collector with a doping of 3 × 10 16 cm −3 . These results are compared with those obtained by using Mazhari and Morkoc's analytical model [6] and Briggs et al's Monte Carlo simulation [8] in figure 2. φ C obtained using equation (7) shows clear signs of saturation at high collector current density and its peak value is comparable to the simulated results obtained by Briggs et al (φ C ≈ 56 mV) and Mushini and Roenker [10] (φ C ≈ 60 mV).…”
Section: Si/sige/si and Gainp/algaas/gainp Dhbtsmentioning
confidence: 88%
“…However, the formation of φ C causes an accumulation of excess electrons in the base edge and an increase in base recombination with a consequent reduction in gain. The simulated results of Briggs et al [8] and Mushini and Roenker [10] showed that, at high current density, this excess electron density at the edge of the base depletion region edge, n B , is comparable with the background doping density. Briggs et al suggested that the extra holes injected into the base to offset this excess electron charge will influence the hole density in the CIB region.…”
Section: Analytical Modelmentioning
confidence: 96%
See 1 more Smart Citation